Human induced rotation and reorganization of the brain of domestic dogs. - Taryn Roberts; Paul McGreevy; Michael Valenzuela (PLoS ONE, 2010)
Domestic dogs exhibit an extraordinary degree of morphological diversity. Such breed-to-breed variability applies equally to the canine skull, however little is known about whether this translates to systematic differences in cerebral organization. By looking at the paramedian sagittal magnetic resonance image slice of canine brains across a range of animals with different skull shapes (N = 13), we found that the relative reduction in skull length compared to width (measured by Cephalic Index) was significantly correlated to a progressive ventral pitching of the primary longitudinal brain axis (r = 0.83), as well as with a ventral shift in the position of the olfactory lobe (r = 0.81). Furthermore, these findings were independent of estimated brain size or body weight. Since brachycephaly has arisen from generations of highly selective breeding, this study suggests that the remarkable diversity in domesticated dogs' body shape and size appears to also have led to human-induced adaptations in the organization of the canine brain.